CHORIONIC VILLI OF THE PLACENTA AT DELIVERY AFTER 40 WEEKS OF GESTATION: MORPHOMETRIC FEATURES - Kozar , Oleh (Collection of scientific papers «ΛΌГOΣ», 2025)
The placenta is a vital organ that ensures the normal development of the fetus during pregnancy [1]. It consists of several structures, including chorionic villi, which are central to the metabolism of substances and gases between mother and child [2]. The morphometry of chorionic villi is an indicator of the functional capacity of the placenta [3]. Studies conducted in recent decades have shown that morphological changes in the villi may be associated with various pathologies of pregnancy, such as delayed fetal growth (IUGR), preeclampsia, and placental insufficiency [4].